HEMATOLOGICAL RESPONSE OF Pangasianodon hypophthalmus FED Cosmos caudatus ENRICHED FEED AND REARED IN SALINE MEDIA - Sahputri, Herliza Khairani; Windarti, Windarti; Efizon, Deni; Kurniawan, Ronal; Karsih, Okta Rizal; Putri, Mega Novia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2025)
Raising striped catfish (Pangasianodon hypophthalmus) in dark conditions with low salinity (5 ppt) can support growth but may also cause stress and affect blood health. Adding Cosmos caudatus leaves, which contain natural bioactive compounds, in fish feed could offer a natural way to help boost the immune system. This study aimed to understand the hematological response of fish toward the C.caudatus enriched feed provision. The fish were reared for 60 days in 5 ppt salinity water and under a controlled photoperiod. There were four treatments: control (no C.caudatus) T1, T2 and T3 (10 g, 20 g, and 30 g of C.caudatus leave powder in 1 kg of feed). Parameters observed were red and white blood cell number, hemoglobin, hematocrit and glucose concentration, phagocytic activity, leukocrit, and types of white blood cells. Results showed that the T1 group significantly improved the ability of red blood cells, hemoglobin, hematocrit, and phagocytosis. Survival rates were high and showed no significant differences between treatments, suggesting that C.caudatus up to 30 g/kg is safe. Based on these findings, a dose of 10 g/kg can be recommended as an effective natural feed additive to help improve the health and immune system of P.hypopthalmus cultured in controlled rearing conditions